Advanced optical receiver architectures for ultra-high capacity but low-cost short-reach optical interconnects - Honglin JI; Xueyang LI; Zhixue HE; Weisheng HU; Shieh William (Dianxin kexue)
The deployment of emerging network infrastructure such as hyper-scale datacenters urgently requires ultra-high capacity but low-cost short-reach optical interconnects.Conventional intensity modulation and direct detection possesses a simple receiver structure but can only recover the intensity information, which restrains the capability of further scaling up the system capacity.Standard coherent detection can deliver high-order modulation formats and achieve high-capacity transmission.Nevertheless, the coherent transceiver requiring expensive narrow-linewidth laser sources and computation-intensive digital signal processing precludes its wide applications in short-reach systems.The advanced direct-detection optical receivers aim to combine the advantages of both direct detection and coherent detection and bridge the gap between them.Therefore, the advanced optical receivers are mainly based on self-coherent detection.Advanced single-polarization, dual-polarization, and few-mode optical receiver architectures wereintroduced.The proposed advanced optical receivers can retrieve the optical field via direct detection without using the narrow-linewidth lasers, which enables the realization of ultra-high capability but low-cost short-reach optical interconnects.